Analysis of Knowledge and Perception of Pregnant Women about Field Massage as an Effort to Prevent Hyperbilirubin in Newborns - Benny Karuniawati (Universitas STRADA Indonesia, 2023)
Hyperbilirubinemia is a clinical phenomenon in 80% of premature babies and 60% of aterm babies in the first week of life (Lei et al., 2018). Field massage is a massage in babies that focuses on stimulating the chest and abdomen area. Field massage is a supporting therapy that can increase the excretion of bilirubin. A good knowledge of field massage can change people's perceptions and perspectives on holistic care in newborns. This study aims to determine the level of knowledge and public perception of field massage. This study used a survey method with a questionnaire. The subjects of the study were pregnant women as many as 62 respondents. The results of the bivariate analysis obtained a significant value of 0.002 which showed that there was a relationship between the level of knowledge and the perception of pregnant women about field massage as an effort to prevent hyperbilirubin in newborns.